2012
DOI: 10.1073/pnas.1217554109
|View full text |Cite
|
Sign up to set email alerts
|

Turning self-destructing Salmonella into a universal DNA vaccine delivery platform

Abstract: We previously developed a biological containment system using recombinant Salmonella Typhimurium strains that are attenuated yet capable of synthesizing protective antigens. The regulated delayed attenuation and programmed self-destructing features designed into these S . Typhimurium strains enable them to efficiently colonize host tissues and allow release of the bacterial cell contents after lysis. To turn such a recombinant attenuated Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 43 publications
3
105
0
Order By: Relevance
“…For example, the recent seminal studies carried out by Curtiss and colleagues have shown the utility of attenuated Salmonella strains as oral vaccine candidates against influenza viruses [7, 26]. Anti-influenza vaccines were constructed based on an attenuated Salmonella mutant with the deletion of sif A gene [7].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the recent seminal studies carried out by Curtiss and colleagues have shown the utility of attenuated Salmonella strains as oral vaccine candidates against influenza viruses [7, 26]. Anti-influenza vaccines were constructed based on an attenuated Salmonella mutant with the deletion of sif A gene [7].…”
Section: Discussionmentioning
confidence: 99%
“…Various steps have been taken to address these criteria, including optimization of the plasmid backbone (origin of replication, backbone size and content, and antibiotic resistance markers), 1824 engineering of the promoter and enhancer regions, 2529 development of improved DNA and mRNA sequences, 13, 3032 and the incorporation of leader and polyadenylation (poly A) sequences. 33 …”
Section: Enhancing Immune Potency Of Dna Vaccinesmentioning
confidence: 99%
“…Synthetic microbes, as a kind of cell therapy, have broad potential for future applications in human disease treatment. For example, bioengineers have been designing various engineered bacteria to perform different specialized functions, such as detection and diagnosis of diseases [75] and production of therapeutics [76] and their delivering [77], which can self-eliminate after therapy [78]. With the development of synthetic biology, the future directions of bacterial cell therapy systems will set a variety of abilities in one and will be smarter as autonomous microbial Bphysicians^ [79].…”
Section: Manipulation Of Motile Microbes: Their Exploitation As Micromentioning
confidence: 99%